Salvodara Persica As An Oral Aids For Edentulous Patients - Mohamed, Nusima; Yacob, Norlela; Wan Ali, Wan Nor Syariza; Ali, Aida (IIUM Medical Journal Malaysia, 2017)
Introduction: Salvadora percisa (popularly known as miswak) has been widely used as an aid for oral hygiene in dentate patient. There is no side effect of using miswak stick. A new approach introduced the role of miswak stick in edentulous patient. It may prevent the incidence of denture stomatitis among denture wearer. This study assessed the effectiveness of the miswak stick as an oral aid in edentulous patients as an alternative treatment for denture stomatitis. Materials and Methods: A clinical case control study included patients affected by denture stomatitis. The Miswak stick was introduced to the subjects to use as the oral device to clean the denture and oral mucosal area everyday. Pre- and postoperative assessment (clinical and photographic) were evaluated within 8 to 12 weeks and analysed by comparing the mapping of denture stomatitis inflammation. Results: A total of 11 subjects with denture stomatitis comprised as type 1; n=5 (46%), type 2; n=4 (36%) and type 3; n=2 (18%). 54.5% of subjects showed more than 50% reduction in the mapping of denture stomatitis inflammation (p<0.05) after the use of miswak stick. This study also showed that the use of miswak stick for more than 3 weeks to Type I and II denture stomatitis (54.6%) has successfully reduce the inflammation for more than 50%. 54.5% of the subjects with good denture hygiene has 50% more reduction of denture stomatitis. Conclusion(s): The miswak stick was significantly effective to reduce the denture stomatitis with a regular use and maintenance of good denture hygiene.